Efektivitas Komunikasi dalam Organisasi - Hassa Nurrohim; Lina Anatan (Jurnal Manajemen Maranatha, 2009)
The need of communication in today’s business competition is continually changing. The advancement of information technology and the changing in managing organization has altered the way that many organizations communicate. The information technology is a tool to communicate with many different groups. The communication process should be managed effectively since not all managers and individu in an organization have good communication skills abd there is an obvious need for training to ensure that they are able to choose the most appropriate communication method to get the message across clearly understood by the receiver and on the other hand, the receiver should be able to supply some feedback.